Test-retest reliability of the Life Satisfaction Questionnaire (LiSat-11) and association between items in individuals with chronic stroke - Elisabeth Ekstrand; Jan Lexell; Christina Brogårdh (Medical Journals Sweden, 2018)
Objective: To evaluate the test-retest reliability of the Life Satisfaction Questionnaire (LiSat-11) and the association between items in individuals with chronic stroke. Design: Test-retest design. Subjects: Forty-five individuals (mean age 65 years) with mild to moderate disability at least 6 months post-stroke. Methods: LiSat-11, which includes 1 global item "Life as a whole" and 10 domain-specific items, was rated on 2 occasions, one week apart. Test-retest reliability was evaluated by kappa statistics, the percent agreement (PA) and the Svensson rank-invariant method. The association between items was evaluated with the Spearman's rank correlation coefficient (rho). Results: The kappa coefficients showed good to excellent agreement (0.59-0.97) and the PA ≤ 1 point was high (> 89%) for all items. According to the Svensson method, a small systematic disagreement was found for "Partner relationship". The other items showed no systematic or random disagreements. All domain-specific items, except one ("Sexual life") were significantly correlated with "Life as a whole" (rhos 0.29-0.80). Conclusion: LiSat-11 is considered reliable and can be recommended for assessing life satisfaction after stroke. The association between items indicates that LiSat-11 measures various aspects that can impact on an individual's life satisfaction.